2023
DOI: 10.3390/cells12020240
|View full text |Cite
|
Sign up to set email alerts
|

The Bronchoprotective Effects of Dual Pharmacology, Muscarinic Receptor Antagonist and β2 Adrenergic Receptor Agonist Navafenterol in Human Small Airways

Abstract: Bronchodilators and anti-inflammatory agents are the mainstream treatments in chronic obstructive and pulmonary disease (COPD) and asthma. The combination of β2 adrenergic receptor (β2AR) agonists and muscarinic antagonists shows superior bronchoprotective effects compared to these agents individually. Navafenterol (AZD8871) is a single-molecule, dual pharmacology agent combining muscarinic antagonist and β2AR agonist functions, currently in development as a COPD therapeutic. In precision-cut human lung slices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Despite significant advances in our knowledge of asthma pathogenesis, the search for better bronchodilators is still evolving. Drugs that inhibit pathways underlying contraction promote relaxation of pre-constricted airways [150,155,162,168,178,180,[203][204][205][206][207], and testing of selective molecules that either elicit or enhance bronchodilation have been used in PCLS [81,[208][209][210][211][212]. Other non-canonical pathways have also been targeted to reverse, or inhibit, airway contraction (specific studies listed in Table 4) [155,165,202,[213][214][215][216][217][218][219][220][221][222][223][224][225][226][227][228].…”
Section: Studies Of Obstructive Lung Diseasesmentioning
confidence: 99%
“…Despite significant advances in our knowledge of asthma pathogenesis, the search for better bronchodilators is still evolving. Drugs that inhibit pathways underlying contraction promote relaxation of pre-constricted airways [150,155,162,168,178,180,[203][204][205][206][207], and testing of selective molecules that either elicit or enhance bronchodilation have been used in PCLS [81,[208][209][210][211][212]. Other non-canonical pathways have also been targeted to reverse, or inhibit, airway contraction (specific studies listed in Table 4) [155,165,202,[213][214][215][216][217][218][219][220][221][222][223][224][225][226][227][228].…”
Section: Studies Of Obstructive Lung Diseasesmentioning
confidence: 99%
“…Dysfunction of the autonomic nervous system is a major contributor to the enhanced bronchospastic activity of the airways in chronic obstructive pulmonary disease (COPD) and asthma, and blocking cholinergic muscarinic receptors and/or stimulating β-adrenergic receptors have proven efficacious in alleviating bronchospastic activity. 3 , 4 …”
Section: A Perspective On “M2 Muscarinic Receptor-dependent Contracti...mentioning
confidence: 99%
“…Targeting muscarinic and β-adrenergic receptors in mono or combined therapies using novel long-acting molecules have been the hallmark treatments to improve breathing in patients with COPD or asthma. 3 , 4 Given that patients with these conditions are normally prescribed with β2 receptor agonists, can novel therapies be developed on the basis of the findings by Alkawadri et al? 7 If confirmed in human, targeting this crosstalk could pose a challenge for patients with cardiovascular diseases such as hypertension, diabetes, cardiac hypertrophy and failure, and coronary artery disease.…”
Section: A Perspective On “M2 Muscarinic Receptor-dependent Contracti...mentioning
confidence: 99%
“…The thromboxane A2 receptor (TXA2 receptor) is a G protein-coupled receptor that primarily modulates platelet aggregation and vascular tone. Yet, the expression of the TXA2 receptor is not limited to platelets and blood vessels; it can be found in a range of tissues, including the heart, lungs, kidneys, and brain (Raychowdhury et al, 1994;Smyth, 2010;Alqarni, 2023;Jude et al, 2023;Eskildsen et al, 2014;Liu et al, 2015;Lagier et al, 2019;Soper et al, 2012). In coronary arteries and cardiac myocytes, activation of the TXA2 receptor leads to vasoconstriction and platelet aggregation (Smyth, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In coronary arteries and cardiac myocytes, activation of the TXA2 receptor leads to vasoconstriction and platelet aggregation (Smyth, 2010). In the respiratory system, the TXA2 receptor is associated with bronchoconstriction and inflammation (Alqarni, 2023;Jude et al, 2023). Activation of the TXA2 receptor in the kidneys has been linked to vasoconstriction and a reduction in renal blood flow (Eskildsen et al, 2014;.…”
Section: Introductionmentioning
confidence: 99%